2009
DOI: 10.1007/s10404-009-0468-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterisation of a modular microfluidic system: coupling magnetic capture and electrochemical detection

Abstract: This work presents the fabrication and characterisation of a versatile lab-on-a-chip system that combines magnetic capture and electrochemical detection. The system comprises a silicon chip featuring a series of microband electrodes, a PDMS gasket that incorporates the microfluidic channels, and a polycarbonate base where 5 permanent magnets are hosted; these parts are designed to fit so that wire bonding and encapsulation are avoided.This system can perform bioassays over the surface of magnetic beads and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The study of peaks generated as a result of enzyme product accumulation during the transition between flow rates reportedly provided increased sensitivity for ␤-galactosidase detection (Godino et al, 2010). In the HRP-HQ system, however, wider peaks and lower initial currents (t = 0) were registered for the highest concentrations of HRP tested, which indicated that part of the BQ produced diffused towards the electrodes during the incubation step.…”
Section: Electrochemical Characterization Of the Microchannel Flow Cellmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of peaks generated as a result of enzyme product accumulation during the transition between flow rates reportedly provided increased sensitivity for ␤-galactosidase detection (Godino et al, 2010). In the HRP-HQ system, however, wider peaks and lower initial currents (t = 0) were registered for the highest concentrations of HRP tested, which indicated that part of the BQ produced diffused towards the electrodes during the incubation step.…”
Section: Electrochemical Characterization Of the Microchannel Flow Cellmentioning
confidence: 97%
“…MPs are then analysed using a flow cell ( Fig. 1), which encloses an incubation microchamber, a microfluidic channel, and a silicon chip containing a set of electrodes (Godino et al, 2010). While MPs are magnetically retained in the microchamber, the enzyme product flows and is chronoamperometrically detected at the gold microband electrode located downstream.…”
Section: Introductionmentioning
confidence: 99%
“…Four permanent magnets (S-04-02-N supermagnete, DE) were located in the holder base, which allows the confinement of MBs inside the microchannels, but upstream from the reference and working electrodes. Following electrochemical detection, the beads were released by blocking the magnetic field using a soft iron slab (Laczka et al, 2011b;Godino et al, 2009). The holder cover contains both the fluidic connections (male mini luer plugs, Ref.…”
Section: Fabrication Of the Measurement Devicementioning
confidence: 99%
“…The flow cell consists of a microfluidic cartridge made of a series of cyclo-olefin polymer (COP) and pressure sensitive adhesive (PSA) layers, featuring four independent channels and their corresponding sets of gold microband electrodes. The cartridge is inserted into a holder that provides microfluidic and electrical connections, and presents a row of switchable magnets (Godino et al, 2009). Except for the microelectrodes, which are microfabricated in the clean room (ICTS-IMB-CNM), the system has been produced using rapid prototyping techniques outside a clean room environment.…”
Section: Introductionmentioning
confidence: 99%
“…Superparamagnetic beads have proven to be well suited for lab-on-a-chip separation of rare cell types 7,8 and highly sensitive bioanalytical measurements [9][10][11][12][13] . Current limitation of this technique are that separation is limited to a small number of analytes and can lead to aggregation of the magnetic beads on the cells, which complicates the recovery of viable rare cell types.…”
mentioning
confidence: 99%